2020
DOI: 10.3390/ma13235471
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic AgPd/UiO-66 Hybrid Catalysts for Propylene Glycol Oxidation into Lactic Acid

Abstract: Different methods (the wetness impregnation of Ag and Pd precursors dissolved in water or acetonitrile solution, and the double solvent impregnation technique) were employed to immobilize Ag–Pd nanoparticles (NPs) into the pores of the microporous zirconium-based metal-organic framework known as UiO-66. The obtained materials were characterized by using nitrogen adsorption-desorption at −196 °C, powder X-ray diffraction, UV-Vis diffusion reflectance spectroscopy, and transition electron microscopy measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The unmodified UiO-66 sample is characterized by a bimodal distribution of micropores with maxima at ~0.9 nm and ~0.6 nm (Figure 4c) that is typical for the UiO-66 [33][34][35]. The observed bimodal distribution is consistent with a change in the size of the pore entrance formed by the terephthalate bridges between the Zr 6 O 4 (OH) 4 sites as a result of a change in the orientation of benzene rings due to the flips around the C 2 symmetry axis [36].…”
Section: Textural Characteristicsmentioning
confidence: 97%
“…The unmodified UiO-66 sample is characterized by a bimodal distribution of micropores with maxima at ~0.9 nm and ~0.6 nm (Figure 4c) that is typical for the UiO-66 [33][34][35]. The observed bimodal distribution is consistent with a change in the size of the pore entrance formed by the terephthalate bridges between the Zr 6 O 4 (OH) 4 sites as a result of a change in the orientation of benzene rings due to the flips around the C 2 symmetry axis [36].…”
Section: Textural Characteristicsmentioning
confidence: 97%
“…MOFs have been employed as support for the incorporation of various metallic and bimetallic nanoparticles. [15][16][17][18][19][20] The tunable pores of MOFs not only prevent the aggregation of metal NPs but also ensure their uniform dispersion. In addition to this, the synergistic effect between metal NPs and MOFs improves the overall stability, selectivity, and activity of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of the PG selective oxidation into carbonyl/carboxylic compounds (methylglyoxal, hydroxyacetone, etc.) are known in the literature for catalysts with supported metal nanoparticles, including Ag [ 5 , 6 , 7 ], Pt [ 8 ] and Pd [ 9 , 10 , 11 , 12 ]. The mechanism of PG conversion was theoretically studied over the Ag 4 cluster [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ], it was suggested that in the case of using the metal/bimetallic catalysts in the oxidation of polyatomic alcohols (e.g., PG and glycerol), the key role of the modifying metal was connected with controlling the reagent bond strength with the catalyst surface without a sharp change in the preferred geometry of the adsorbate, and such changes of binding energies can have a strong impact on the catalytic properties. Transition metals, such as Bi for Pd-Bi supported catalysts [ 12 ], are often used as a modifying metal added to those of the Pt or Au subgroups.…”
Section: Introductionmentioning
confidence: 99%